Análisis de la aplicación del método contable frente al factor de proporcionalidad en el cálculo del uso del crédito tributario del impuesto al valor agregado (IVA), en las empresas comerciales del cantón Latacunga en el año 2021. - Jiménez Tonato, Dayana Micaela (2023)
The objective of this research project is methods application authorized by the current regulations for tax calculation credit liquidation of added value tax (VAT), in commercial companies of Latacunga canton in the 2021 year. The applied methodology has a quantitative approach, descriptive and explanatory type and for analysis development proceeded to documentary modality, the sample subject to analysis of 137 companies that are under ISIC section G. The review of provided database by IRS allowed to determine that 121 commercial companies applied proportionality factor, while only 12% used accounting method. However, after applying simulation to reported data by companies in question, it was determined that there is a greater benefit for taxpayer by accounting method application, thus increasing the item that represents the tax credit in its favor. The results show that, when applying accounting method is to 121 companies that calculated the tax credit under proportionality factor, the following items were recorded: $ 286, 957,685.77 while companies that applied the proportionality factor under the accounting method were recorded with a value of $117, 570,488.42, which shows a value of $ 286, 957,685.77. 488.42, which is evidenced at data analysis from the VAT returns of commercial companies of Latacunga canton where a benefit level of $169, 387,197.35 is recorded, which is equivalent to 59%. In conclusion, the use of the proportionality factor in calculating tax credit is frequently used because it is intrinsic in form 104; however, there is a lack knowledge of accounting method.